Functional performance of the main lighting system of motor vehicles - Kachmar, Roman; Zhuk, Roman (Lviv Politechnic Publishing House, 2017)
Visual perception plays a crucial role in the safety of road users. However, certain conditions such as twilight, the impact of bad weather, dirty windshields, etc. have a negative impact, which in turn increase the likelihood of traffic accidents (TAs) [1]. The ever increasing number of vehicles on the road is an additional potential danger. In response to these factors work is constantly being done to modernize existing and develop new lighting devices. Vehicular headlights are firstly assigned to optimally illuminate the roadbed in order to ensure safety [2]. For this reason headlights, including their light source, are important safety elements for vehicles, and their application requires official permission. The type and location of vehicular lighting, as well as their design, light source, color and light settings are regulated by law [3]. Automakers pay sufficient attention to the fuel economy and safety of their vehicles. So for this reason automotive light sources, such as incandescent and gas-discharge (HID) bulbs, are increasingly being replaced by LED and laser diode bulbs as they provide superior lighting with lower power consumption. This in turn leads to increased vehicle safety and economy [3].
Keywords: vehicle; lighting system; headlights; lamp; low beam; illumination; power supply; diffuser; blinding oncoming drivers